Effie Karageorgos, Australian Soldiers in South Africa and Vietnam: Words from the Battlefield (Historia, 2021)
In the last couple of years, the Bloomsbury Studies in Military History (with the renowned military historian, Jeremy Black as series editor), has produced some twenty thought-provoking publications that offer scholarly accounts of various aspects of military history. Thus far, war in Africa has not been the subject of any of the studies, but Effie Karageorgos (who teaches at the University of Melbourne in Australia) has changed that, albeit that her study deals only partially with conflict on the African continent and the focus of her study is on Australian soldiers’ experiences (in South Africa during the Anglo-Boer War of 1899 to 1902, and in Vietnam, where Australia was involved from 1962 until 1973).
Keywords: Bloomsbury Studies; Military History; Australia; Melbourne; Anglo-Boer; Vietnam